The Opportunistic Reporting of Material Events and the Apparent Misconception of Investors' Reaction - SEGAL, Dan (Institutional Knowledge at Singapore Management University, 2013)
Using a comprehensive sample of non-earnings 8-K filings from 1996 to 2011, we examine whether firms engage in opportunistic reporting of mandatory and voluntary news. We find strong evidence of opportunistic reporting of negative news, especially among public firms. Public firms are more likely to delay disclosure of negative news, report negative news after trading hours, and report on the last day of the week. We also find evidence of opportunistic bundling of news. Our findings support the notion that managers engage in strategic disclosure by delaying or obfuscating negative news in order to mitigate the potential market reaction. Factors such as the risk of litigation, information asymmetry, and corporate governance influence reporting behavior. Further analysis of the market reaction to opportunistic disclosure uncovers no evidence of investor inattention or under-reaction.